A New Sulfur and Carbon Degassing Inventory for the Southern Central American Volcanic Arc: The Importance of Accurate Time‐Series Data Sets and Possible Tectonic Processes Responsible for Temporal Variations in Arc‐Scale Volatile Emissions. (12th December 2017) - de Moor, J. M.; Kern, C.; Avard, G.; Muller, C.; Aiuppa, A.; Saballos, A.; Ibarra, M.; LaFemina, P.; Protti, M.; Fischer, T. P.
Abstract: This work presents a new database of SO2 and CO2 fluxes from the Southern Central American Volcanic Arc (SCAVA) for the period 2015–2016. We report ∼300 SO2 flux measurements from 10 volcanoes and gas ratios from 11 volcanoes in Costa Rica and Nicaragua representing the most extensive available assessment of this ∼500 km arc segment. The SO2 flux from SCAVA is estimated at 6, 240 ± 1, 150 T/d, about a factor of three higher than previous estimations (1972–2013). We attribute this increase in part to our more complete assessment of the arc. Another consideration in interpreting the difference is the context of increased volcanic activity, as there were more eruptions in 2015–2016 than in any period since ∼1980. A potential explanation for increased degassing and volcanic activity is a change in crustal stress regime (from compression to extension, opening volcanic conduits) following two large (Mw > 7) earthquakes in the region in 2012. The CO2 flux from the arc is estimated at 22, 500 ± 4, 900 T/d, which is equal to or greater than estimates of C input into the SCAVA subduction zone. Time‐series data sets for arc degassing need to be improved in temporal and spatial coverage to robustly constrain volatile budgets and tectonic controls. Arc volatile budgets are strongly influenced by short‐lived degassing events and arc systems likely display significant short‐term variations in volatile output, calling for expansion of nascent geochemical monitoring networks to achieve spatial and temporal coverage similar to traditional geophysical networks. Plain Language Summary: We show that volcanoes in Central America are more active now than any time in the scientific record, and explore possible causes. Key Points: We present an extensive new data set for Central American volcanic gas emission rates Higher gas fluxes are observed for 2015–2016 than in previous studies, calling for expansion of gas monitoring networks Higher gas fluxes are related to increased arc‐wide volcanic activity and may be related to megathrust earthquakes